Eating behaviour, body image perception and its associated factors among primary school students in Kota Bharu, Kelantan - @ Azmira, Fazilawati Ab Latiff (2017)
Objective The awareness of body image perception among children and adolescent had increasing trend in recent years. The dissatisfaction of body image has always been associated with unhealthy eating behaviour, sex and body weight. The objectives of this study were to identify eating behaviour and to identify body image perception and its associated factors among primary school students in Kota Bharu, Kelantan. Design This was a cross sectional study conducted from March to April 2015 in seven randomly selected primary schools in Kota Bharu involving 776 students from standard Five and Six. Material and Methods This study used a guided self-administered questionnaire which was adapted from Adolescent Food Habit Checklist (AFHC) to assess the eating behaviour and Childress Contour Drawing Rating Scale to evaluate body image perception. Height and body weight were measured to determine the body mass index (BMI). BMI was categorised as normal, underweight and overweight/obese according to the World Health Organisation (WHO). Results The mean age of the students was 11.2 year-old with 57.1% of them were females. Among the students, 51.3% had less healthy eating behaviour with mean AFHC score of 13.15 (SD3.44) while 60.1% had body image dissatisfaction with sex and Body Mass Index